An improved lifetime prediction method for metallized film capacitor considering harmonics and degradation process. (November 2020) - Lv, Chunlin; Liu, Jinjun; Zhang, Yan; Lei, Wanjun; Cao, Rui
Abstract: Metallized film capacitor (MFC) is one of the stand-out components in terms of failure rate in power electronic converters. However, the influence of harmonics and degradation process on MFC are not well described by the conventional lifetime prediction method, causing a large gap between prediction result and engineering practice. Therefore, this paper further explores the aging failure mechanisms of MFC and proposes an improved lifetime prediction method. The function mechanism that the harmonics change the partial discharge inside MFC to affect lifetime is expounded, which is modelled by several influence factors. Moreover, the coupling relationship of hot-spot temperature and equivalent series resistor (ESR) aging is discussed by an improved aging model based on the parameter drift of ESR. The capacitance degradation curve obtained from this model are consistent with the experimental results, verifying the validity of this method. Highlights: Verify the correctness of the results and analysis Explain the availability of simplified thermal models Add more results in the case study section Modify some less rigorous statements